Aptamer‐Array‐Guided Protein Assembly Enhances Synthetic mRNA Switch Performance. (13th July 2022) - Lu, Qiuyu; Hu, Yaxin; Yin Li, Cheuk; Kuang, Yi
Abstract: Synthetic messenger RNA (mRNA) switches are powerful synthetic biological tools that can sense cellular molecules to manipulate cell fate. However, their performances are limited by high output signal noise due to leaky output protein expression. Here, we designed a readout control module that disables protein leakage from generating signal. Aptamer array on the switch guides the inactive output protein to self‐assemble into functional assemblies that generate output signal. Leaky protein expression fails to saturate the array, thus produces marginal signal. In this study, we demonstrated that switches with this module exhibit substantially lower signal noise and, consequently, higher input sensitivity and wider output range. Such switches are applicable for different types of input molecules and output proteins. The work here demonstrates a new type of spatially guided protein self‐assembly, affording novel synthetic mRNA switches that promise accurate cell manipulation for biomedical applications. Abstract : Output signal noise, resulting from leaky protein expression, hampers the ability of synthetic mRNA switches to accurately manipulate cellular functions. Using an aptamer array as a scaffold to guide the formation of a functional protein assembly, a readout control module was designed that only allows output signal generation when the output protein is expressed in a sufficiently large amount to facilitate self‐assembly on the aptamer array. Synthetic mRNA switches with this module exhibit low‐to‐no signal noise and better performance in cells.